Biosynthesized Silver Nanoparticles Demonstrate Hepatoprotective Biochemical Safety in Female Wistar Rats - Suhad Khalid Sgheer; Ali Tariq Abdul Hassan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Silver nanoparticles (AgNPs) are widely applied in biomedical and technological fields, yet conventional chemical and physical synthesis methods raise safety and environmental concerns. Specific Background: Biosynthesis using probiotic bacteria such as Lactobacillus rhamnosus has emerged as a green alternative with potential biocompatibility advantages. Knowledge Gap: Limited in vivo evidence exists regarding the biochemical and histological safety of biosynthesized AgNPs, particularly their hepatic effects. Aims: This study aimed to evaluate the biochemical and histological effects of AgNPs biosynthesized by L. rhamnosus in female Wistar albino rats. Results: Biosynthesized AgNPs significantly reduced liver enzymes (ALT, AST, and ALP), significantly increased vitamin B12 levels, showed no significant change in body weight, and preserved normal liver tissue architecture. Novelty: The study demonstrates the hepatic safety profile of L. rhamnosus–mediated AgNPs in vivo compared with risks reported for conventionally synthesized AgNPs. Implications: These findings support probiotic-mediated biosynthesis as a safer and environmentally friendly approach for developing silver nanoparticles for biomedical applications.Keywords : Biosynthesized Silver Nanoparticles, Lactobacillus rhamnosus, Green Nanoparticle Synthesis, Liver Enzyme Biomarkers, Wistar Albino RatsHighlight : Significant reductions in AST, ALT, and ALP without alterations in body mass. Serum vitamin B12 concentrations increased markedly following 30-day administration. Liver histology preserved normal architecture, indicating absence of hepatocellular damage.